Is there an Aboriginal bioethic?. Issue 6 (30th November 2004) - Garvey, G; Towney, P; McPhee, J R; Little, M; Kerridge, I H
Abstract : It is well recognised that medicine manifests social and cultural values and that the institution of healthcare cannot be structurally disengaged from the sociopolitical processes that create such values. As with many other indigenous peoples, Aboriginal Australians have a lower heath status than the rest of the community and frequently experience the effects of prejudice and racism in many aspects of their lives. In this paper the authors highlight values and ethical convictions that may be held by Aboriginal peoples in order to explore how health practitioners can engage Aboriginal patients in a manner that is more appropriate. In doing so the authors consider how the ethics, values, and beliefs of the dominant white Australian culture have framed the treatment and delivery of services that Aboriginal people receive, and whether sufficient effort has been made to understand or acknowledge the different ethical predispositions that form the traditions and identity of Aboriginal Australia(ns).